OP0030 Corticosteroid bridging strategies with methotrexate monotherapy in early rheumatoid and undifferentiated arthritis; a comparison of efficacy and toxicity in the treach and improved studies. (12th June 2018) - van der Pol, J.A.; Brilman, E.G.; de Jong, P.H.; Weel, A.E.; Hazes, J.M.; Huizinga, T.W.; Allaart, C.F.
Abstract : Background: What is the optimal glucocorticoid (GC) bridging therapy with MTX monotherapy in early arthritis? Objectives: To compare short term clinical efficacy of high and low dose GC tapering schedules with MTX monotherapy in 2 clinical trials in early rheumatoid arthritis (RA) and undifferentiated arthritis (UA) patients. Methods: In tREACH, early RA and UA (arthritis in ≥1 joint(s), <1 year symptoms) patients were randomised to 3 different treatment arms. For this analysis we only use the data of arm C: oral GCs (prednisone) (15 mg/day, tapered to 0 in 10 weeks) with MTX monotherapy (25 mg/week); low dose GC tapering schedule (LDGC). In IMPROVED RA and UA (arthritis in ≥1 joint and ≥1 other painful joint, <2 years symptoms) patients were treated with prednisone (60 mg/day, tapered in 7 weeks to 7.5 mg/day, continued to 4 months)+MTX monotherapy (25 mg/week); high dose GC tapering schedule (HDGC). We compared%DAS-remission (<1.6) and low disease activity (≤2.4) at first evaluation (3 months tREACH, 4 months IMPROVED) and DAS and HAQ over time. After multivariate normal imputation we applied generalised estimating equations (GEE) for linear outcomes and logistic regression models for binary outcomes, adjusted for potential baseline confounders (figure 1). Adverse events were compared between treatment arms using χ2-square tests. Results: Patients with a HDGC (n=610) had shorter symptom duration and higher HAQ, were less often seropositive (ACPA positive 56.0% vs 77.3%, RF positive 58.1% vs 65%) and more often had UA (20.3% vs 2.1%) than patients with a LDGC (n=97). Baseline DAS was comparable. At the first evaluation time point (median 3.06 (IQR 2.99–3.22) months in LDGC, 4.01. (3.8–4.17) in HDGC) DAS and HAQ had decreased significantly less after 3 months LDGC: DAS β (95% CI) 0.500 (0.276; 0.725), and HAQ 0.330 (0.189; 0.470) than after 4 months HDGC (figure 1). Compared to the HDGC patients, patients with the LDGC had a significantly lower chance of achieving DAS-remission 63.4% vs 28.9% (OR (95% CI) 0.215 (0.124; 0.373) and low disease activity 80.6% vs 55.7% ((OR (95% CI) 0.249 (0.143; 0.435)). Presence of ACPA was positively associated with achieving DAS-remission in the HDGC group, but not in the LDGC group. Per 100 patient years, 7.98 serious adverse events were reported in the HDGC and 23.4 in the LDGC (p=0.004). Hypertension, hyperglycemia (>7.8 mmol/L), gastrointestinal complaints and liverenzymes above normal were reported in similar frequencies across all groups. In patients with a LDGC more headaches, skin rashes, creatinine above normal range and any decrease in haematology blood counts were reported (data not shown). Conclusions: In early arthritis patients, GC bridging therapy with prednisone 60 mg daily tapered in 7 weeks to and continued at 7.5 mg daily in combination with MTX monotherapy was associated with better clinical outcomes and without additional effects than prednisone 15 mg daily tapered to nil in 10 weeks in combination with MTX monotherapy, after correction for baseline age, gender, DAS, body mass index, presence of ACPA, presence of rheumatoid factor, symptom duration, and (in GEE) time from baseline. Disclosure of Interest: J. van der Pol: None declared, E. Brilman: None declared, P. de Jong: None declared, A. Weel Grant/research support from: tREACH study was supported by an unrestricted grant from Pfizer bv. [0881–1 02 217]. Pfizer had no involvement in study design; in collection, analysis and interpretation of data; writing of the report and decision to submit for publication., J. Hazes: None declared, T. Huizinga: None declared, C. Allaart Grant/research support from: The work was supported by AbbVie during the first year of the IMPROVED study. Study design, data collection, trial management, data analysis and preparation of the manuscript were performed by the authors.